MEMO: IAPG FUNDING - MOZINGO RL (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Roger Mozingo to Samuel Chilcote concerning the costs of a tobacco industry scientific witness program (IAPAG). Argues the importance and effectiveness of a program preparing scientists for testimony especially in the legislative arena.